Tematizando o esporte à luz da pedagogia freireana nas aulas de educação física escolar - Silva, Antonio Jansen Fernandes da (2025)
Sport has become one of the most widespread cultural manifestations throughout the world, whether for the daily practice of different communities and people or for the world of entertainment. In view of this, the research thesis is that Freire's pedagogy can contribute to the thematization and problematization of Sport in School Physical Education classes, favoring collaborative, dialogic, contextualized, hopeful, ethical, critical and autonomous work on the part of those involved in educational action, which contrasts the banking education developed in Sports with a technical and reproductive bias, and can provide a more fair, egalitarian, democratic society and tolerant of differences. The general objective of the study is to analyze the process of thematization and problematization of a Sports educational project in School Physical Education classes from a Freirean dialogic perspective. In this study, the qualitative action research method was used, with a 9th year elementary school class from the public education network in Fortaleza. The following instruments were used to collect data: a) participant observation of School Physical Education classes, through the use of a field diary; b) Dialogical Reflective Circle; c) record of School Physical Education classes; d) portfolio of students; e) self-assessment. The Discursive Textual Analysis method was used to analyze the data. The study findings were: a) contextualization is a fundamental principle for developing Sport from a Freirean perspective; b) there are several challenges and possibilities for discussing Sports in the school context; c) the Dialogical Reflective Circle can be used as an instrument for revisiting and evaluating the educational process. It is possible to infer that the development of Sport in an authentic and contextualized way can help in the deconstruction of traditional Sport installed in the school context. Likewise, Freirean pedagogy has a lot to contribute to the development of Sports in School Physical Education classes, mainly due to its critical, reflective, dialogical, problematizing, autonomous, libertarian, emancipatory bias, among others, favoring a less socially unfair society, exclusionary and intolerant of differences.